SPH Technique to Study the Sloshing in Concrete Liquid Tanks - Seyyed Meisam Aghajanzadeh; Hasan Mirzabozorg; Homayon Yazdani (Numerical Methods in Civil Engineering)
This study aims to consider the sloshing height and hydrodynamic pressure in roofless and roofed liquid storage tanks utilizing a coupled FE-SPH technique. As a design technique for determining the necessary analyses and main parameters to reach reasonable results, the Taguchi method is used. The SPH formulation models the liquid concerning the large amplitude sloshing waves, and the finite element method simulates the structure. At first, it is found that expressions presented in ACI 350.3-06 should be revised when calculating the sloshing height in a rectangular tank. Secondly, when determining the hydrodynamic pressure applied on the roof and, also the sloshing height, the frequency content of the input ground motion affects significantly the contained liquid responses. Comparison of the results obtained for roofed and roofless tanks indicate no clear correlation between their dynamic responses. The results of this study suggest the ratio of liquid height to its length, the length itself, and earthquake record PGA as noise parameters in Taguchi analysis. At last, the suggested Taguchi analysis’s main design parameters for future studies are the acceleration spectrum intensity ASI and the liquid’s height in the storage tank.